Squamous Cell Carcinoma (SCC) in Brown meagre (Sciaena umbra Linnaeus, 1758), a new candidate species for aquaculture in Mediterranean - KOLYGAS, M.N.; LAMPOU, E.; DOUKAS, D.; TONTIS, D.; PAPPAS, I.S.; GOURZIOTI, E.; BAKOPOULOS, V.; KAKAVA, E.; ATHANASSOPOULOU, F. (Journal of the Hellenic Veterinary Medical Society, 2020)
A case of epithelial tissue tumors on the body of two adult Brown meagres (Sciaena umbra Linnaeus, 1758) is reported. Brown Meagre population of 20.000 was imported to sea cages on September of 2003 at 3g, to check the potential use of this species as a new candidate in Mediterranean aquaculture. The population had been kept for 8 years to serve as a genetic pool for further zootechnical investigation. The main pathology observed after 8 years in the sea cages were mainly ocular lesions (cataract) possibly due to natural aging and/or long culture period under high natural light intensity (UV radiation) and/or net injuries at a percentage of 1,32% of total cultured population. Apart from that, on two fish, reddish- white tumorous growths were evident on skin, macroscopically. Histologically, the timorous growths were diagnosed as Squamous cell carcinoma. Numerous rounded pearls and nests of epidermal proliferated cells were evident, some of which had a non-cellular center. There were also foci of necrosis and irregular deposits of keratin within the tumor tissue. Special stains (Ayoub-Shklar, Haematoxylin-Eosin & Schiff’s Periodic Acid) were applied to the tissue for comparison. To our knowledge this is the first presented report of SCC in this species.